Sustainable Operations Management in Hospitality: An Empirical Study of Energy Efficiency and Waste Reduction Strategies - Handayani, Tri (Politeknik Siber Cerdika Internasional, 2025)
The hospitality industry faces mounting pressure to enhance sustainability performance amid escalating environmental degradation, resource depletion, and operational costs. Hotels are resource-intensive establishments that consume substantial energy and generate considerable waste through continuous 24-hour operations and high guest turnover. This study investigates the implementation and effectiveness of integrated energy-efficiency and waste-reduction strategies within hotel operations, addressing the persistent gap between environmental intentions and operational practices today. Employing a cross-sectional design, this research utilizes Structural Equation Modeling (SEM) and multiple regression analysis on primary data from 150 hotel managers across Indonesian properties. The measurement instrument demonstrates robust validity through Confirmatory Factor Analysis (factor loadings: 0.68-0.89, AVE: 0.58-0.72) and reliability (Cronbach's ?: 0.81-0.89, Composite Reliability: 0.82-0.90). Results reveal that energy-efficiency practices (?=0.47, p<0.001, R²=0.34) and waste-reduction strategies (?=0.52, p<0.001, R²=0.41) significantly enhance operational performance. The integrated sustainability model demonstrates superior explanatory power (R²=0.57), with waste reduction exerting a more substantial effect (?=0.44) than energy efficiency (?=0.31). Hotels implementing formal sustainability policies consistently outperform non-policy hotels across all performance dimensions. This research provides empirical evidence on integrated operational frameworks, performance-based sustainability assessment, and applicability in emerging economies. Findings underscore that coordinated energy and waste management initiatives constitute essential pathways toward operational resilience and competitive advantage in hospitality operations.